Measurement and evaluation of the hydrodynamics and secondary currents in and near a strait connecting large water bodies - A field study - Guler, Isikhan; Yuksel, Yalcin; Yalciner, Ahmet Cevdet; Cevik, Esin; Ingerslev, Christian (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The straits connect two large water bodies show highly strong and stratified currents related to meteorological, morphological and hydrodynamic conditions. In some cases, spatial and temporal changes of the stratified currents and their thickness, direction and magnitude are so complex. This complexity directly affects the circulation pattern in the region, water exchange between both ends of the straits and migration of fish species. In order to understand general characteristics of this kind of straits and identifying the complexity of the hydrodynamics of the region and evaluate the secondary currents and recirculation need long term, intensive, field work and measurement studies. As an example of this kind of hydrodynamically complex straits, Bosphorus strait is selected for a field study. The Bosphorus strait has a strongly stratified two-layer system and a unique case of the maximal exchange regime typical of strait flows, which is largely determined by conditions at the Black Sea. Although the Bosphorus strait has distinct two-layer stratification with an associated two-layer system exchange, no continuous current measurements have been made so far, previous measurements all having been random sampling. In this paper, a detailed measurement program has been applied to Bosphorus strait. In the measurement program, a short-term current profile measurement at selected locations at southern part of the strait has been conveyed. Additionally a long-term measurement of current profile has been performed at a selected critical location (in front of the Dolmabahce Palace) where a recirculation flow exists in the strait. The scope of this paper is to present the techniques and the results of analysis of measurement data. In the measurements the current profile (magnitude and direction) has been determined at every I m depth intervals from the surface to the sea bottom at 3 min duration at every hour. Measurements provide that lower-layer flows in northward direction from the Sea of Marmara towards the Black Sea, whereas the upper-layer flow comes from the Black Sea and flows towards the Sea of Marmara in the opposite direction of lower layer. The Bosphorus strait exhibits distinctive features associated with variations in its width and depth. The meandering features of Bosphorus also cause recirculation flows. These results of measurements are presented, discussed and compared with previous studies. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: bosphorous; current; stratified; Engineering; Oceanography